2011
DOI: 10.1128/mcb.05312-11
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes in mTERT+/− and mTERT−/− Mice Are Due to Short Telomeres, Not Telomere-Independent Functions of Telomerase Reverse Transcriptase

Abstract: Telomerase is essential for telomere length maintenance. Mutations in either of the two core components of telomerase, telomerase RNA (TR) or the catalytic protein component telomerase reverse transcriptase (TERT), cause the genetic disorders dyskeratosis congenita, pulmonary fibrosis, and other degenerative diseases. Overexpression of the TERT protein has been reported to have telomere length-independent roles, including regulation of the Wnt signaling pathway. To examine the phenotypes of TERT haploinsuffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
106
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(113 citation statements)
references
References 82 publications
(137 reference statements)
5
106
2
Order By: Relevance
“…But this finding is challenged by other studies, which did not confirm this function of hTERT. 45,46 Our results show that hTERT is a direct target gene of β-catenin and indicate, thereby, that the Wnt signaling pathway controls self-renewal and telomerase activity at the same time, 47 thereby linking two essential components in the biology of colorectal cancers.…”
Section: Discussionmentioning
confidence: 92%
“…But this finding is challenged by other studies, which did not confirm this function of hTERT. 45,46 Our results show that hTERT is a direct target gene of β-catenin and indicate, thereby, that the Wnt signaling pathway controls self-renewal and telomerase activity at the same time, 47 thereby linking two essential components in the biology of colorectal cancers.…”
Section: Discussionmentioning
confidence: 92%
“…In mice mTERT +/− and mTERT −/− on the CAST/ EiJ genetic background, TERT overexpression in some settings may activate the Wnt pathways (Strong et al 2011). However, loss of function in a physiological setting has no apparent effects on Wnt signalling (Strong et al 2011).…”
Section: R133 Review a Pestana And Others Tert Biology And Function Imentioning
confidence: 99%
“…However, loss of function in a physiological setting has no apparent effects on Wnt signalling (Strong et al 2011). This deficiency leads to telomere shortening, that limits tissue renewal, and these effects are not telomereindependent functions of TERT (Strong et al 2011).…”
Section: R133 Review a Pestana And Others Tert Biology And Function Imentioning
confidence: 99%
“…However, the proposed noncanonical role of TERT in the Wnt/β-catenin signaling cascade has been controversial. Several studies have reported a lack of physical association of TERT with BRG1 or β-catenin (Listerman et al, 2014), as well as no apparent effect of TERT deficiency on phenotypes associated with Wnt signaling in TERT-knockout mice (Strong et al, 2011). Although TERT appears to regulate the expression of growth-promoting genes, this event might not be solely promoted by Wnt signaling.…”
Section: Introductionmentioning
confidence: 99%